PENGARUH EXTENSIBLE BUSINESS REPORTING LANGUAGE (XBRL), SALES GROWTH, LEVERAGE, DAN FIRM SIZE TERHADAP KINERJA PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Ariena Alifia Suseno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the effect of XBRL, Sales growth, Leverage, and Firm Size to Firm Performance through with Good Corporate Governance. This study was conducted This study focused on consumer goods businesses listed on the Indonesia Stock Exchange between 2018 and 2022. Data were analyzed using multiple linear regression analysis methods and Moderate Regression Analyze (MRA) with the help of Eviews 13 program. The results showed that XBRL, Sales growth, Leverage, and Firm Size have a significant positive effect simultaneously on Firm Performance. However, Good Corporate Governance variable cannot moderate the effect of Sales growth, Leverage, and Firm Size on Firm Performance.